Analysis of Community Satisfaction with Public Services at the Population and Civil Registration Office of Seluma Regency - Meirio Pratama; Neri Susanti; Nenden Restu Hidayah (Journal of Indonesian Management, 2023)
The purpose of this study was to determine public satisfaction with public services in the Seluma Regency Population and Civil Registration Service. The sample in this study was 100 respondents, namely the people of Seluma Regency. Data collection uses observation, interviews, questionnaires and documentation. The analysis method used is IKM in this study based on KEPMENPAN Number 4 of 2007 concerning Guidelines for Preparing Community Satisfaction Surveys. From the results of the study, it was found that the quality of service at the Seluma Regency Population and Civil Registry Office has met the expectations of customers or the community, in other words, the community is satisfied with the services provided by the Seluma Regency Population and Civil Registry Office office with the criteria "Very Good (A)" which is indicated by the average value of the mastarakat perception of 3.64 at an interval of 3.5324 – 4.00. The Community Satisfaction Index (IKM) value of 3.64 is at an interval of 3.5324 – 4.00 with the criterion "Very Good (A)", as well as the IKM value after being converted by 91 is at an interval of 88.31 – 100.00 with the criterion "Excellent (A)". Based on 9 indicators of service quality, the highest value is in the fourth indicator, namely costs / tariffs with an average value of 3.74 at intervals of 3.5324 – 4.00 with the criterion "Excellent (A)". Based on 9 indicators of service quality, the lowest value is in the sixth indicator, namely the competence of the Executor with an average value of 3.35 at intervals of 3.0644 – 3.532 with the criterion "Good (B)".